Accounting Conservatism, Capital Intensity, Financial Distress, and Tax Avoidance in Manufacturing: Konservatisme Akuntansi, Intensitas Modal, Kesulitan Keuangan, dan Penghindaran Pajak pada Perusahaan Manufaktur - Erva Rudianti; Sigit Hermawan (Academia Open, 2023)
This research aims to analyze the influence of accounting conservatism, capital intensity, and financial distress on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2019. The sample consists of 44 observations obtained through purposive sampling. Multiple regression analysis is used to examine the effect of each variable on tax avoidance. The empirical results reveal that capital intensity and financial distress have a significant impact on tax avoidance, while accounting conservatism does not. This study contributes to the existing literature on tax avoidance and supports previous research conducted in this area. It provides insights into the factors influencing tax avoidance behavior in manufacturing companies, offering implications for policymakers, regulators, and practitioners in enhancing tax compliance and corporate governance practices. Highlights: Determinants of tax avoidance: Investigating the influence of accounting conservatism, capital intensity, and financial distress on tax avoidance behavior in manufacturing companies. Empirical analysis: Examining the significance of these variables through multiple regression analysis to understand their impact on tax avoidance. Implications for taxation and corporate governance: Providing insights for policymakers, regulators, and practitioners to enhance tax compliance and corporate governance practices in manufacturing companies, based on the findings related to tax avoidance determinants. Keywords: accounting conservatism, capital intensity, financial distress, tax avoidance, manufacturing companies